RETRACTED: Ecology and safety in the field of national economy - Ananyeva Ekaterina; Bondarenko Ivan; Frolovskaia Julia; Kurbatova Galina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001